Systemic inflammation and Alzheimer's disease. (20th July 2011) - Holmes, Clive; Butchart, Joe
Abstract : A number of studies demonstrate disturbances of the central innate immune system in AD (Alzheimer's disease). In animal and human studies, there is evidence of close communication between systemic and central innate immune systems. Animal models of neurodegeneration show evidence of an exaggerated central innate immune response following systemic inflammation. Clinical studies of AD show evidence of increased cognitive decline and exaggerated sickness behaviour in response to systemic inflammation. Recognition of this communication pathway offers alternative explanations for a number of recognized risk factors in the development and progression of AD and highlights the potential of the manipulation of systemic innate immunity as a novel therapeutic approach.